CREG1 deficiency impaired myoblast differentiation and skeletal muscle regeneration - Haixu Song; Xiaoxiang Tian; Lianqi He; Dan Liu; Jiayin Li; Zhu Mei; Ting Zhou; Chunying Liu; Jiaqi He; Xiaodong Jia; Zheming Yang; Chenghui Yan; et al. (Wiley, 2024)
Abstract Background CREG1 (cellular repressor of E1A‐stimulated genes 1) is a protein involved in cellular differentiation and homeostasis regulation. However, its role in skeletal muscle satellite cells differentiation and muscle regeneration is poorly understood. This study aimed to investigate the role of CREG1 in myogenesis and muscle regeneration. Methods RNA sequencing data (GSE8479) was analysed from the Gene Expression Omnibus database (GEO, https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi). We generated Creg1 knockdown and skeletal muscle satellite cells specific Creg1 overexpression mice mediated by adeno‐associated virus serotype 9 (AAV9), skeletal muscle mature myofibre Creg1 knockout mice (myoblast/Creg1MKO), and control mice Creg1flox/flox (Creg1fl/fl) as in vivo models. The mice were injected into tibialis anterior (TA) muscle with 100 μL of 10 μM cardiotoxin to establish a muscle regeneration model. Creg1fl/fl and Creg1MKO mice were treated with AAV‐sh‐C‐Cbl (2 × 1010 genomic copies/mouse) to silence C‐Cbl in the TA muscle. 293T and C2C12 cells were transfected with plasmids using lipofectamine RNAi MAX in vitro. Mass spectrometry analyses and RNA sequencing transcriptomic assay were performed. Results We analysed the transcriptional profiles of the skeletal muscle biopsies from healthy older (N = 25) and younger (N = 26) adult men and women in GSE8479 database, and the results showed that Creg1 was associated with human sarcopenia. We found that Creg1 knockdown mice regenerated less newly formed fibres in response to cardiotoxin injection (~30% reduction, P < 0.01); however, muscle satellite cells specific Creg1 overexpression mice regenerated more newly formed fibres (~20% increase, P < 0.05). AMPKa1 is known as a key mediator in the muscle regeneration process. Our results revealed that CREG1 deficiency inhibited AMPKa1 signalling through C‐CBL E3‐ubiquitin ligase‐mediated AMPKa1 degradation (P < 0.01). C‐CBL‐mediated AMPKa1 ubiquitination was attributed to the K48‐linked polyubiquitination of AMPKa1 at K396 and that the modification played an important role in the regulation of AMPKa1 protein stability. We also found that Creg1MKO mice regenerated less newly formed fibres compared with Creg1fl/fl mice (~30% reduction, P < 0.01). RNA‐seq analysis showed that CREG1 deletion in impaired muscles led to the upregulation of inflammation and DKK3 expression. The TA muscles of Creg1MKO mice were injected with AAV‐vector or AAV‐shC‐Cbl, silencing C‐CBL (P < 0.01) in the skeletal muscles of Creg1MKO mice significantly improved muscle regeneration induced by CTX injury (P < 0.01). Conclusions Our findings suggest that CREG1 may be a potential therapeutic target for skeletal muscle regeneration.